Świadomość czy algorytm? Ludzkie maszyny jako emanacje Frankensteina Mary Shelley w naukach kognitywnych oraz tekstach kultury - Saja , Krystian (Przestrzenie Teorii, 2020)
Mary Shelley’s Frankenstein is without doubt a popular science-fiction novel, which has inspired many generations of artists and creators in popular culture and mass culture. It has also become an inspiration for scientific studies in the field of robotics and cybernetics. Modern cognitive sciences are looking for the perfect pattern that will allow artificial intelligence to be achieved. An important problem for scientists was the lack of full knowledge about consciousness. We are able to recreate the structure of the human body in a machine, but we are not able to fully simulate the neural processes that would create human consciousness. This problem is perfectly illustrated by cultural works, including literature and cinematography. We see in them both the emanations of the motifs contained in Shelley’s novel and the realization of scientific hypotheses that shape our image of a conscious, thinking machine.